2022
DOI: 10.3389/fchem.2022.872117
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress on Revealing 3D Structure of Electrocatalysts Using Advanced 3D Electron Tomography: A Mini Review

Abstract: Electrocatalysis plays a key role in clean energy innovation. In order to design more efficient, durable and selective electrocatalysts, a thorough understanding of the unique link between 3D structures and properties is essential yet challenging. Advanced 3D electron tomography offers an effective approach to reveal 3D structures by transmission electron microscopy. This mini-review summarizes recent progress on revealing 3D structures of electrocatalysts using 3D electron tomography. 3D electron tomography a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 118 publications
(166 reference statements)
0
3
0
Order By: Relevance
“…3D electron tomography for electrocatalysts has been review recently. 155 Among various applications of 3D electron tomography, we use MOFs as a typical example to demonstrate the advantages of 3D electron tomography. Zheng and colleagues 156 studied the impact of surfactants on the morphology of synthesized ZIF-coated Au@Ag nanorods, where electron tomography was used to reveal the 3D structures.…”
Section: D Electron Tomographymentioning
confidence: 99%
See 1 more Smart Citation
“…3D electron tomography for electrocatalysts has been review recently. 155 Among various applications of 3D electron tomography, we use MOFs as a typical example to demonstrate the advantages of 3D electron tomography. Zheng and colleagues 156 studied the impact of surfactants on the morphology of synthesized ZIF-coated Au@Ag nanorods, where electron tomography was used to reveal the 3D structures.…”
Section: D Electron Tomographymentioning
confidence: 99%
“…Afterwards, the grid is washed and dried, and subjected to TEM investigation by focusing on the previously studied catalysts. 155,204 Shokhen et al 205 found that during potential cycles to simulate degradation under operando conditions of the fuel cell, Pt particles grew through Ostwald ripening, migration and coalescence, while the carbon substrate remained stable. Under conditions that simulated fuel cell shutdown and startup, the carbon substrate degraded through volume loss and collapse, which forced the Pt nanoparticles to merge and to grow (Fig.…”
Section: Deactivation: (Quasi-)in Situ Tem Study During the Electroch...mentioning
confidence: 99%
“…These tomography experiments range from analyzing stereo pairs over a small or large tilt range, to recording many projection directions over a tilt range spanning up to 180°, to performing ex situ or even in situ experiments where many projection directions are recorded from a sample over multiple time points during a structural transformation. Kübel et al (177) have reviewed STEM tomography in detail, Miao et al (28) have reviewed atomic-resolution electron tomography, Hata et al (178) have reviewed applications of diffraction-contrast STEM and deformation characterization tomography in materials science, and Wang et al (30) have reviewed electron tomography of catalyst NPs. Wolf et al (179) have examined the possibilities for using STEM tomography in biological imaging.…”
Section: D Tomographymentioning
confidence: 99%